Islam dan realitas sosial di mata intelektual Muslim Indonesia - Mahmud, Amir (Jakarta, Indonesia : Edu Indonesia Sinergi, 2005)
Thoughts of Indonesian Muslim intellectuals on Islam and social conditions in Indonesia
Includes bibliographical references
In Indonesian, and one article in English
Keywords: Islam -- Indonesia; Social change -- Indonesia; Indonesia -- Civilization